An enzyme found in amitochondriate eukaryotic organisms, NAD(P)H oxidoreductase One simpler homologue of the enzyme found in vertebrates is Giardia lamblia. (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2023)
The enzyme glQR, found in the amitochondriate eukaryotic protozoan Giardia lamblia, catalyses the two-electrontransfer oxidation of NAD(P)H using a quinone as an acceptor. G. lamblia expressed the gene for this protein inEscherichia coli. The NAD(P)H oxidoreductase activity was present in the purified recombinant protein, and it wasmore effective at donating electrons than NADH. The enzyme's substrates included menadione, naphthoquinone, anda number of synthetic electron acceptors. glQR is quite similar in amino acid sequence to other vertebrate homologuesand to a number of putative bacterial proteins.The secondary structural parts of glQR are similarly organised in threedimensional modelling, despite the fact that it is much smaller than mammalian enzymes. Enzymes in mammals havea high degree of conservation among their amino acid residues that are involved in substrate binding and catalysis.Since glQR shares these characteristics with other members of this protein family as well as similarities in substrateselectivity and inhibitor sensitivity, it may be confidently called a member of this family.